PENURUNAN TINGKAT KEMATIAN IKAN GURAMI MELALUI PENURUNAN KEKERUHAN AIR KOLAM DENGAN PROSES ELEKTROKOAGULASI - Widjajanto, Danang; Saepudin, Endang (Universitas Mataram, 2025)
The turbidity of the water used for cultivating gourami fish by the Mina Lestari Fish Farmers group reaches 68 NTU and oxygen solubility is about 2.5 mg/L, while the maximum turbidity permitted for fish farming is 50 NTU and oxygen solubility more than 5 mg/L. Insufficient oxygen can cause the death of fish. To reduce water turbidity can be treating water using electrocoagulation. This community service activity aims to implement aelectrocoagulation process to reduce water turbidity, thereby increasing dissolved oxygen levels and reducing gourami mortality in RW 05, Duren Mekar, Depok. The methods used include site surveys, problem identification, partner coordination, program outreach, water reservoir for electrocoagulation process construction, coagulant producer construction, elctrocoagulation processing and evaluation. The electrocoagulation water reservoir for electrocoagulation process is made from concrete with 3m long, 1.5 m wide, and 1.2 m high. It is equipped with one 4-inch PVC pipe for the inlet and three 3-inch PVC pipes for the outlet. The electrocoagulation process is carried out by flowing 5 liters per minute of coagulant from coagulant storage to the water in reservoir. The electrocoagulation process was able to reduce water turbidity from 68 NTU to 43 NTU and increase dissolved oxygen from 2.5 mg/L to 5.6 mg/L as well as reduce the gourami fish deaths from 20 to 5 from a cultivation of 100 fish for 5 months. The conclusion is that the electrocoagulation process of pond water is able to produce water with turbidity that meets the requirements for cultivating gourami fish.